(untitled) (Acta Entomologica Serbica, 2010)
The entomological collection of the National Museum of Bosnia and Herzegovina is one of the oldest Balkan insect collections. Eighty-seven (87) dragonfly specimens from 19 species that originate from Bulgaria were found in this collection. In this paper we present the oldest and till now unknown records of dragonflies from Bulgaria from this collection. Some interesting and new distribution data on several species are also presented and discussed.